Blinding properties of methods for supplying drug kits to investigational sites - Ron Yu (Contemporary Clinical Trials Communications, 2015)
Most blinded, late stage, randomized clinical trials package study drug, active or placebo, into drug kits for distribution to investigational sites. Drug kits enable investigators to administer study drug to subjects in a blinded manner without the assistance of an unblinded pharmacist. Supply methods determine when and how many kits to send to sites. If not properly designed, these methods can partially unblind investigators, i.e., investigators can conclude that two subjects are (1) on the same treatment arm with certainty or (2) on different treatment arms with certainty. Partial unblinding can bias the way investigators provide patient care, report adverse events and assess efficacy endpoints, and can lead to full unblinding when the other subject is unblinded. In this paper, we describe several examples of partial unblinding in the supply methods commonly used by many Randomization and Trial Supply Management (RTSM) systems, propose a new criterion for evaluating the blinding properties of supply methods, and prove that two alternative supply methods do not permit full or partial unblinding, even after the investigator is unblinded up to a certain number of other subjects.